PENGARUH PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X IPA 3 SMAN 1 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Yuliana, Cindy; Hamdunah, Hamdunah; Muslim, Audra Pramitha (Universitas PGRI Sumatera Barat, 2021)
The background of this research are the low ability of students’ understanding mathematical concepts and student learning outcomes are below of minimum completeness criteria (KKM) where 75 for mathematic lesson in SMAN 1 Enam Lingkung. The purpose of this research is to determine the effect of cooperative learning type Student Teams Achievement Division (STAD) on the ability to students’ understanding mathematical concepts of class X IPA 3 SMAN 1 Enam Lingkung. This research used a One Shot Case study research design with purposive sampling method. The research sample was class X IPA 3 SMAN 1 Enam Lingkung. The research instrument used was the final test (post-test) in the form of essay questions. The data analysis technique used is the t-test. Hypothesis test result obtained thitung = 2,27 and ttabel = 2,03, because based on the results of the calculation, Ho is rejected so that the hypothesis in this research is accept. Because the hypothesis was accepted, it was concluded that there was an effect of cooperative learning type Student Teams Achievement Division (STAD) on the ability to students’ understanding mathematical concepts of class X IPA 3 SMAN 1 Enam Lingkung, Padang Pariaman Regency.